Pengaruh Brand Trust Terhadap Keputusan Menginap Di The Axana Hotel Padang - Dedek Kurniawan; Feri Ferdian (Jurnal Manajemen Pariwisata dan Perhotelan, 2023)
The general purpose of this study is to analyze the influence of Brand Trust on the decision to stay at The Axana Hotel Padang. The type of research used in this study is a quantitative approach and causal associations. Guests who have stayed at Axana Hotel Padang participated in the study. The sample consisted of 204 guests who followed a nonvoluntary review strategy. The data collection strategy uses Likert scale surveys that attempt to explore speculation. Data for this study were processed using SPSS 26.00. The results of this study prove that Brand Trust is in the appropriate category (80%). In addition, the decision to stay on the category is enough ie. (75%). Brand Trust had a significant effect on overnight decisions with an R-squared value of 0.397 and a significance of 0.000 < 0.05. This means that there are 0.603 that are influenced by other factors.